2019
DOI: 10.1177/1088868319855783
|View full text |Cite
|
Sign up to set email alerts
|

Are Collectivistic Cultures More Prone to Rapid Transformation? Computational Models of Cross-Cultural Differences, Social Network Structure, Dynamic Social Influence, and Cultural Change

Abstract: Societies differ in susceptibility to social influence and in the social network structure through which individuals influence each other. What implications might these cultural differences have for changes in cultural norms over time? Using parameters informed by empirical evidence, we computationally modeled these cross-cultural differences to predict two forms of cultural change: consolidation of opinion majorities into stronger majorities, and the spread of initially unpopular beliefs. Results obtained fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 93 publications
0
57
0
Order By: Relevance
“…Such models, often used in biology, are increasingly implemented in social and cultural psychology to model long-term population-level processes. These agent-based models are used to generate testable hypotheses in domains that defy easy logical analysis (e.g., models of complex social influence dynamics and their implications for cultural evolution; Muthukrishna & Schaller, 2020; for additional social psychological applications, see Smith &Conrey, 2007, andJackson, Rand, Lewis, Norton, &Gray, 2017).…”
Section: Computational Modelingmentioning
confidence: 99%
“…Such models, often used in biology, are increasingly implemented in social and cultural psychology to model long-term population-level processes. These agent-based models are used to generate testable hypotheses in domains that defy easy logical analysis (e.g., models of complex social influence dynamics and their implications for cultural evolution; Muthukrishna & Schaller, 2020; for additional social psychological applications, see Smith &Conrey, 2007, andJackson, Rand, Lewis, Norton, &Gray, 2017).…”
Section: Computational Modelingmentioning
confidence: 99%
“…Social influence is a direct assessment of the price supporting green marketing that includes the influence of other people that are relevant and in a larger context, namely, the influence of the organization decision. There are two tactics of social influence, namely reciprocal relations and social evidence, which are used to increase the influence of societal orientation behavior that results in synergistic potential for their feeling and highlight of their directions of social impacts (Argo & Dahl, Young, 2009) [22][23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Social Influencementioning
confidence: 99%
“…Other work has found that people give less money to those who are more socially distant (unknown) friends of friends in standard economic games (Candelo, Eckel, & Johnson, 2018;Goeree, McConnell, Mitchell, Tromp, & Yariv, 2010). Computational modeling methods have also been used to show that there is quicker consolidation of majority opinion and more successful spread of initially unpopular beliefs in populations characterized by their greater susceptibility to social influence (Muthukrishna & Schaller, 2019).…”
Section: Example #2: Revisiting Influence and Information Transmissionmentioning
confidence: 99%